Spinal hevin mediates membrane trafficking of GluA1-containing AMPA receptors in remifentanil-induced postoperative hyperalgesia in mice. (23rd March 2020) - Wang, Zhen; Tao, Yuzhu; Song, Chengcheng; Liu, Peng; Wang, Chunyan; Li, Yize; Cui, Wei; Xie, Keliang; Zhang, Linlin; Wang, Guolin
Highlights: Remifentanil infusion produced mechanical and thermal pain hypersensitivity and exacerbated incision-induced hyperalgesia. Hevin and membrane trafficking of GluA1-containing AMPA receptors in the dorsal horn of the spinal cord were increased after administration of remifentanil, and they further increased after combination of remifentanil with incision, indicating they were contributor to remifentanil induced postoperative hyperalgesia. Inhibition of spinal Hevin via the intrathecal injection of Hevin-sh-RNA reduced overexpression of Hevin and membrane trafficking of GluA1-containing AMPA receptors after combination of remifentanil with incision, and therefore prevented remifentanil-induced postoperative pain hypersensitivity. Intrathecal injection of exogenous Hevin elicited hyperalgesia and the membrane trafficking of GluA1-containing AMPA receptors, which were reversed by the delivery of NASPM. This suggests hevin in the dorsal horn of spinal cord participates in the membrane trafficking of GluA1-containing AMPA receptors. Abstract: Introduction: Hevin, a matricellular protein involved in tissue repair and remodeling, is crucial for initiation and development of excitatory synapses. Besides, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPA) is an ionotropic transmembrane receptor for glutamate that mediates fast synaptic transmission in the central nervous system (CNS). This study aimed to investigate the correlation between spinal Hevin and AMPA receptors in remifentanil-induced postoperative hyperalgesia in mice. Methods: Remifentanil (1.33 μg/kg/min for 60 min) was subcutaneously injected into a mouse model of postoperative pain. The von Frey and hot plate tests were performed to assess mechanical and thermal hyperalgesia. The gene and protein expression of Hevin and the membrane trafficking of GluA1-containing AMPA receptors in the dorsal horn of spinal cord were detected by quantitative reverse transcription polymerase chain reaction (RT-qPCR) and Western blot analysis. In addition, Hevin-shRNA, exogenous Hevin, and 1-naphtylacetyl-spermine (NASPM) were administrated intrathecally to assess the relationship between spinal Hevin and AMPA receptors. Results: Perioperative administration of remifentanil can aggravate and prolong incision-induced mechanical and thermal hyperalgesia. Treatment with remifentanil increased the expression of spinal Hevin and the membrane trafficking of AMPA receptors. Additionally, knockdown of spinal Hevin attenuated pain hypersensitivity and downregulated membrane trafficking of AMPA receptors after treatment with remifentanil. Meanwhile, preadministration of NASPM reversed spontaneous pain and membrane trafficking of spinal GluA1-containing AMPA receptors induced by exogenous Hevin in naïve mice. Conclusions: Spinal Hevin was involved in the maintenance of remifentanil-induced postoperative hyperalgesia via modulating membrane trafficking of AMPA receptors.